2013
DOI: 10.1093/ntr/ntt059
|View full text |Cite
|
Sign up to set email alerts
|

Pictorial Health Warnings on Cigarette Packages in Qatar: Preimplementation Awareness and Perceptions of Ever-Smokers Versus Never-Smokers

Abstract: These findings suggest the needs for increased awareness about the value of PHWs and call for further research to determine the effectiveness of PHW labels on cigarette packages in Qatar and greater Middle Eastern region, where legislations on PHWs are still at infancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 11 publications
0
18
0
Order By: Relevance
“…[4] In a study from Qatar, 55% and 67% of the urban population was found be aware of pictorial health warnings (PHWs) and text warnings respectively. [5] Acknowledging the lower literacy rate of the Indian population in rural areas, it can well be expected that the awareness levels will be lower. A Mexican study showed that having seen health warnings increased the awareness regarding even less well-known health risks of smoking.…”
Section: Introductionmentioning
confidence: 99%
“…[4] In a study from Qatar, 55% and 67% of the urban population was found be aware of pictorial health warnings (PHWs) and text warnings respectively. [5] Acknowledging the lower literacy rate of the Indian population in rural areas, it can well be expected that the awareness levels will be lower. A Mexican study showed that having seen health warnings increased the awareness regarding even less well-known health risks of smoking.…”
Section: Introductionmentioning
confidence: 99%
“…There has been a major political commitment to tobacco control in the GCC countries from a legislative perspective as well as a public health one (11)(12)(13)(14), but much more still needs to be done, particularly with regard to further public education and research (15,16). Sustaining such commitment is key to capitalizing on the progressive momentum which many of these countries are now experiencing.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, it was found that pictorial health warnings on cigarette packages were significantly associated with increased awareness of smoking-related health hazards and behavior amendment. 17 Exposure to tobacco advertising, promotion, and sponsorship (TAPS) is found to be linked to the initiation and continuation of smoking among young individuals. The World Health Organization (WHO) Framework Convention on Tobacco Control (FCTC) recommends countries to prohibit all forms of TAPS.…”
Section: Discussionmentioning
confidence: 99%